Cork carries coffee. - Avery, Tim (Packaging Digest, 2008)
The article reports on the new material for hot beverage cup sleeves from Memphis, Tennessee-based company CoolCorC. The company is now selling hot beverage cup sleeves made out of cork. Cofounders and brothers, Larry Wright and Josh Wright, states that their newly developed product protects the hand from hot a lot better than the existing paper sleeves.
Keywords: COOLCORC (Company); Cork; DRINKING cups; MEMPHIS (Tenn.); TENNESSEE; WRIGHT